PENINGKATAN PEMAHAMAN SISWA DI SD KERTOBANYON KABUPATEN MADIUN TERHADAP HATE SPEECH ATAU UJARAN KEBENCIAN PRESPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG ITE - Meirza Aulia Chairani; Krista Yitawati; Bambang Sukarjono (JURNAL DAYA-MAS, 2024)
The writing of this service journal aims to increase the understanding of students at SD Kertobanyon Madiun Regency on hate speech or hate speech in the perspective of Law Number 1 of 2024 concerning ITE, so that students know the sanctions if they make hate speech Hate speech on Social Media. The method used is to conduct legal counseling at SDN Kertobanyon with a team of lecturers. This counseling provides knowledge to teachers and students about social media. Where social media is like a double-edged coin, one side provides benefits on one side provides badness. Nowadays, the use of gadgets for children is a natural thing, parents who do not accompany children to the effects of using gadgets will cause bad things, for example, children make hate speech on social media by speech or writing and cause sara issues, destruction, division and uproar in society. Many children do not understand the effects that will be obtained if they commit hate speech on social media. In the development of the ITE Law, there is an article on hate speech with a criminal sanction of 6 years. The juvenile justice process can be subject to diversion if the child is the perpetrator in a legal case that is different from adult justice.